The nurture assumption : why children turn out the way they do / Judith Rich Harris. - Harris, Judith Rich (Bloomsbury, 1999)
How much credit do parents deserve when their children turn out well? How much blame when they turn out badly? This book explodes some of our deepest beliefs and gives us something radically new to put in their place.